Metacognition Awareness and Its Correlation with Academic Achievement of Educational Students - ELFA ERIYANI (Indonesian Research Journal in Education |IRJE|, 2020)
This study aimed to describe the metacognitive awareness of Indonesian Language and Literature Educational students in STKIP YPM Bangko, and to differentiate student metacognition by gender and length of study, and to correlate metacognition awareness on student achievement indexes. A quantitative research design was used with population of 80 students in academic year of 2017-2018. A purposive sampling technique was taken by involving students of the third, fifth, and seventh semester. Documentations and questionnaires were used as the instuments of this study and manual calculations and SPSS 16.0 for Windows were used to analyze the collected data in the study. The results showed that there was no significant difference between metacognitive awareness of male and female students, and between metacognitive awareness of the second year, the third year, and the fourth year. The latest, there was a very weak positive relationship between metacognitive awareness and students’ achievement.